2020
DOI: 10.1007/s12597-020-00469-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact on bullwhip effect in food industry due to food delivery apps

Abstract: Every supply chain whether services, durable goods or customer goods, is drifting more and more towards E-supply chain using Internet Technology (IT).Such supply chains make use of internet for selecting items, placing their orders and making payments too. Now days the E-supply chain for serving food items is getting very popular because of ease and facilities provided by Food Delivery Apps (FDAs) like Swiggy, Zomato and Uber Eats etc. Use of FDAs has caused variation in demand of food items and subsequently h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Few authors have researched the benefits perceived by loyalty programs or incentives on FDAs (Jain et al , 2020; Kapoor and Vij, 2018; Koiri et al , 2019; Tomacruz and Flor, 2018). These incentives could be coupons to be used at a later stage or loyalty discounts, rewards and cashback offers (Kapoor and Vij, 2018; Koiri et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Few authors have researched the benefits perceived by loyalty programs or incentives on FDAs (Jain et al , 2020; Kapoor and Vij, 2018; Koiri et al , 2019; Tomacruz and Flor, 2018). These incentives could be coupons to be used at a later stage or loyalty discounts, rewards and cashback offers (Kapoor and Vij, 2018; Koiri et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among the FDAs factors responsible for processing the demand, signals and price fluctuations, discount offers, availability of comparative prices and ease of choice are the prime exhibits (Jain et al , 2020; Saad, 2020). According to Market Watch (2019), attractive discounts, rewards and cashback offers are factors that increase the popularity of FDAs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…One reason for this may be is they have taken into account the whole manufacturing SME sector of Egypt. On the other hand, in our study food processing and food manufacturing sector is selected, which is product-oriented and customer-oriented (Jain et al ., 2021), and product orientation leads to a competitive advantage. Moreover, studies reported a significant positive relationship between SCA and SBP (Haseeb et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…With 16% of all papers (16 out of 97), a strong focus is placed on the sharing of quality and transparent data and information along the supply chain. Most of the papers see joint decisions from sharing as a competitive advantage (Jain et al, 2021); however, B€ uy€ uk€ ozkan and G€ oçer (2018) argue that often information about supply chains operations is held locally, which undermines effective and efficient collaboration among members along the supply chain. As a response, Soosay and Hyland (2015) emphasize that members along the supply chain have to establish an appropriate level of trust and integrate supply chain processes to achieve performance improvements through collaboration.…”
Section: Collaborationmentioning
confidence: 99%